A Systematic Evaluation of State Laws Governing Optometric Glaucoma Management in the United States Upto 2015. Issue 3 (March 2018) - Chodnicki, Kevin; Kalarn, Sachin; Quinn, Laura; Jampel, Henry; Saeedi, Osamah
Abstract : Purpose: To describe state laws that govern the optometric practice of glaucoma management in the United States and to correlate those laws with state demographics upto 2015. Materials and Methods: We performed a cross-sectional ecological study of the 50 United States and the District of Columbia. Regulations governing optometric scope of practice as written by each state Board of Optometry were reviewed. Specific optometric privileges assessed included: ability to manage glaucoma independently, use of diagnostic pharmaceutical agents, use of therapeutic pharmaceutical agents (including topical and oral steroids and other oral pharmaceutical agents), IV injections, intraocular injections, therapeutic lasers, presence of defined referral, and comanagement guidelines, and hours of yearly continuing education needed for glaucoma management. Optometric privilege was compared with demographic and employment information for each state. Results: Optometrists in all states, except for Massachusetts, and the District of Columbia are allowed to manage glaucoma; 16 states have defined comanagement guidelines. Therapeutic lasers are allowed in 3 states: Kentucky, Louisiana, and Oklahoma. States with defined comanagement guidelines had a mean of 6.9±1.9 ophthalmologists per 100, 000 people, significantly more than the 5.3±1.1 in states without defined comanagement of glaucoma ( P <0.01). Binary logistic regression showed that, accounting for population and area, the higher the number of optometrists in a state, the less likely there is to be defined comanagement [β (SE)=−0.008 (0.003), P =0.02] and the greater the number of ophthalmologists in a given state, the more likely a state has defined comanagement [β (SE)=−0.13 (0.006)]. Conclusions: There is a diversity of regulations that govern optometric management of glaucoma in each of the 50 states and the District of Columbia. The number of optometrists and ophthalmologists in a state may influence state regulations governing optometric practice and referral guidelines. Abstract : Supplemental Digital Content is available in the text.